2021
DOI: 10.3390/cancers13215427
|View full text |Cite
|
Sign up to set email alerts
|

Liver Decompensation as Late Complication in HCC Patients with Long-Term Response following Selective Internal Radiation Therapy

Abstract: Selective internal radiation therapy (SIRT) is used as a treatment for hepatocellular carcinoma (HCC). The aim of this study was to assess long-term liver-related complications of SIRT in patients who had not developed radioembolization-induced liver disease (REILD). The primary outcome was the percentage of patients without REILD that developed Child-Pugh (CP) ≥ B7 liver decompensation after SIRT. The secondary outcomes were overall survival (OS) and tumor response. These data were compared with a matched coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In a retrospective analysis, patients with Child–Pugh score A and ALBI grade 2 were at substantially higher mortality risk due to hepatic dysfunction after RE than patients with ALBI grade 1 [ 30 ]. Previous studies confirmed ALBI score as a helpful predictor of hepatic deterioration after RE [ 30 , 31 ]. However, it still harbors several pitfalls in tumor patients, such as inflammation and malnutrition, that can undoubtedly influence relevant parameters such as albumin as an integral part of those scores.…”
Section: Discussionmentioning
confidence: 84%
“…In a retrospective analysis, patients with Child–Pugh score A and ALBI grade 2 were at substantially higher mortality risk due to hepatic dysfunction after RE than patients with ALBI grade 1 [ 30 ]. Previous studies confirmed ALBI score as a helpful predictor of hepatic deterioration after RE [ 30 , 31 ]. However, it still harbors several pitfalls in tumor patients, such as inflammation and malnutrition, that can undoubtedly influence relevant parameters such as albumin as an integral part of those scores.…”
Section: Discussionmentioning
confidence: 84%
“…We conducted full-text reviews of 50 potentially eligible articles, and 41 articles were excluded for not reporting relevant outcomes. Finally, our NMA included 9 original articles, with a total of 1954 patients [ 13 16 , 20 24 ]. The selection process for the study is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We included 7 [ 13 , 14 , 20 24 ] studies with SIRT and sorafenib interventions, and first conducted a systematic pairwise meta-analysis of these 7 studies. A record of OS is available for all 7 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although decreased liver function could be due to tumor progression, potential negative effects of the anti-tumor treatment itself could also have contributed. Similarly, a recent study comparing transarterial radioembolization and sorafenib with the aid of propensity score matching analyses [47] identified decreased liver function after the radioembolization as an important negative prognostic factor. In that study, only liver decompensation occurring longer than four months post-treatment was taken into account (with the rationale to exclude earlier decompensation due to radiation-induced liver disease).…”
Section: Discussionmentioning
confidence: 99%